Does freeze‐all policy affect IVF outcome in poor ovarian responders?. (3rd September 2018) - Roque, M.; Valle, M.; Sampaio, M.; Geber, S.
ABSTRACT: Objective: To evaluate whether the freeze‐all strategy affects in‐vitro fertilization (IVF) outcome in poor ovarian responders (POR) defined according to the Bologna criteria. Method: This was a retrospective cohort study of patients undergoing IVF treatment between January 2012 and December 2016 at a single center. A total of 433 POR (as defined by the Bologna criteria) fulfilled criteria and were included in the study; of these, 277 patients underwent fresh embryo transfer (ET) and 156 followed the freeze‐all policy. All patients underwent controlled ovarian stimulation (COS) following a gonadotropin‐releasing hormone antagonist protocol, and cleavage‐stage ET. Main outcome measure was ongoing pregnancy rate. Secondary outcomes included implantation and clinical pregnancy rates. The freeze‐all strategy was implemented when the progesterone serum level was > 1.5 ng/mL or the endometrium was < 7 mm on the trigger day, or as per patient preference. Patients with previous failed fresh ET also underwent fresh ET or freeze‐all strategy considering the indications mentioned above. Results: Mean maternal age in the freeze‐all group was 39.5 ± 3.6 years and in the fresh ET group was 39.7 ± 3.8 years ( P = 0.54). Mean number of embryos transferred (nET) was 1.53 ± 0.6 and 1.60 ± 0.6 ( P = 0.12) in the freeze‐all and fresh ET groups, respectively. Ongoing pregnancy rate did not differ significantly between the freeze‐all and fresh ET groups (9.6% vs 10.1%, respectively; relative risk (RR), 0.95; 95% CI, 0.52–1.73), nor did the clinical pregnancy rate (14.1% vs 13.7%, respectively; RR, 1.03; 95% CI, 0.63–1.67). Implantation rate was 9.6% and 9.8% ( P = 0.82) in the freeze‐all and fresh ET groups, respectively. Logistic regression analysis (including maternal age, antral follicle count, number of retrieved and mature oocytes, nET, and fresh ET vs freeze‐all strategy) indicated that maternal age ( P < 0.001) and nET ( P = 0.039) were the only independent variables associated with ongoing pregnancy rate. Conclusions: The freeze‐all strategy, compared with fresh ET, had no impact on IVF outcomes in POR patients as defined according to the Bologna criteria. Multicenter studies including large numbers of patients should be carried out to confirm the results of this study and reach conclusions about the potential benefits of the freeze‐all policy for poor responders. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.